Psychology and psychopathology related to leadership - José Manuel Bertolín Guillén; Patricia De Retes Candenas (INFAD)
Introduction. This brief, panoramic contribution deals with the psychology and psychopathology of leaders and followers of various types and fields. Material and method. Scope review based on the relevant, detailed documentary search in PubMed and Google Scholar until January 2025, from which n= 94 references considered the most relevant have been selected. Results and discussion. The question of leadership is complex and ambiguous, so for practical purposes it will henceforth be assimilated into the concepts of leadership, management and others. The heterogeneous findings and the appropriate qualitative interpretative considerations are summarised below. The personalities of leaders and followers are interdependent. It has been documented that the exaltation of leadership attracts and legitimises the preferences of the more narcissistic audience, and that followers or subordinates often develop a flexible psychology that allows them to accept different leaders in different contexts. The mental and behavioural dysfunctions, traits and disorders of historical leaders often form a complicated web of adaptive and maladaptive behavioural characteristics. Among leaders, it is hypothetically not uncommon to find personality patterns that are considered dark. For its part, authoritarian leadership is positively related to unethical follower behaviour. Ideally, leadership, in which leader–follower interpersonal neural synchronisation is proven, should be helpful and ethical, as well as supported by neuroscientific knowledge. Conclusions. A gap in adequate up-to-date research knowledge on the psychology and psychopathology of leaders and followers was revealed, which requires further research.